2017
DOI: 10.1016/j.envpol.2017.04.023
|View full text |Cite
|
Sign up to set email alerts
|

PBDEs (polybrominated diphenyl ethers) pose a risk to captive giant pandas

Abstract: The Qinling subspecies of giant panda (Ailuropoda melanoleuca qinlingensis), is highly endangered; fewer than 350 individuals still inhabit Qinling Mountains. Previous research revealed captive pandas were exposed to bromine, so we hypothesized that captive pandas were exposed to and affected by polybrominated diphenyl ethers (PBDEs). To test this hypothesis, we tested blood and feces of captive and wild pandas, their drinking water, food (bamboo leaves) from SWARC (Shaanxi Wild Animal Research Center)and FNNR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…com/link") (pink area in Figure 2 With rapid industrialization, environmental pollution is increasing and following a similar trajectory to that previously seen in developed countries (Seinfeld 2004). Recent studies also have revealed that captive pandas are exposed to high concentrations of toxic chemicals, including PCDDs (polychlorinated didenzo-p-dioxins), PCDFs (polychlorinated dibenzofurans), PCBs (polychlorinated biphenyls), PBDE (polybrominated diphenyl ethers), and heavy metals (Chen et al 2016;Chen et al 2017a;Chen et al 2017b;Chen et al, forthcoming). A detailed study of the Qinling subspecies demonstrated that exposure to Figure 2.…”
Section: Captive Panda Populations Face Their Own Risksmentioning
confidence: 99%
“…com/link") (pink area in Figure 2 With rapid industrialization, environmental pollution is increasing and following a similar trajectory to that previously seen in developed countries (Seinfeld 2004). Recent studies also have revealed that captive pandas are exposed to high concentrations of toxic chemicals, including PCDDs (polychlorinated didenzo-p-dioxins), PCDFs (polychlorinated dibenzofurans), PCBs (polychlorinated biphenyls), PBDE (polybrominated diphenyl ethers), and heavy metals (Chen et al 2016;Chen et al 2017a;Chen et al 2017b;Chen et al, forthcoming). A detailed study of the Qinling subspecies demonstrated that exposure to Figure 2.…”
Section: Captive Panda Populations Face Their Own Risksmentioning
confidence: 99%
“…Additionally, heavy metal pollutants (Cd, Pb, As, Hg, and other elements) are found in the soil, water, staple food (bamboo), and feces of giant pandas in their habitat in the Qinling Mountains, which are mainly the result of coal burning, garbage burning, and traffic pollution sources [12]. Meanwhile, high levels of pollutants have been detected in a giant panda's body [13], which were related to abnormalities of alanine aminotransferase, lactate dehydrogenase, total bilirubin, etc., in the giant panda's body [14,15]. The wild giant panda habitats are inaccessible and far away from the main areas of human activity, and administrators strictly manage their habitats.…”
Section: Introductionmentioning
confidence: 99%
“…The subspecies' survival is threatened by habitat fragmentation, epidemics, bamboo 6 / 38 flowering, human activities (such as road network construction, solid waste, industrial activities, etc.) and harmful pollutants (Chen et al, 2016;Chen et al, 2017;Zhao et al, 2019). The contamination of water, soil, and vegetation (especially bamboo) by OCs is of great concern because of the possible risk to giant pandas and other wildlife.…”
Section: Introductionmentioning
confidence: 99%